Pseudogenes as a paradigm of neutral evolution - Li, W H; Gojobori, T; Nei, M (Nature (London), 1981)
On the neutral mutation hypothesis, the rate of nucleotide substitution is expected to be higher for functionally less important genes or parts of genes than for functionally more important genes, as the latter would be subject to stronger purifying (negative) selectio. On the other hand, selectionists believe that most nucleotide substitutions are caused by positive darwinian selection, in which case the rate of nucleotide substitution in functionally unimportant genes or parts of genes is expected to be relatively lower because the mutations in these regions of DNA would not produce any significant selective advantages. Kimura and Jukes have argued that the higher substitution rate observed at the third positions of codons than at the first two positions supports the neutral mutation hypothesis, as most third-position substitutions are synonymous and do not change the amino acids encoded, although others have discussed the possibility that third-position substitutions are subject to positive darwinian selection. Recently, Kimura noted that the mouse globin pseudogene, psi alpha 3, evolved faster than the normal mouse alpha 1 gene, although he did not compute the substitution rate. Here, we present a method of computing the rate of nucleotide substitution for pseudogenes, and report that the three recently discovered pseudogenes show an extremely high rate of nucleotide substitution. As these pseudogenes apparently have no function, this finding strongly supports the neutral mutation hypothesis.